Phenotypic Characterization of the KK/HlJ Inbred Mouse Strain - Berndt, A. (2013)
Detailed histopathological diagnoses of inbred mouse strains are important for interpreting research results and defining novel models of human diseases. The aim of this study was to histologically detect lesions affecting the KK/HlJ inbred strain. Mice were examined at 6, 12, and 20 months of age and near natural death (ie, moribund mice). Histopathological lesions were quantified by percentage of affected mice per age group and sex. Predominant lesions were mineralization, hyperplasia, and fibro-osseous lesions. Mineralization was most frequently found in the connective tissue dermal sheath of vibrissae, the heart, and the lung. Mineralization was also found in many other organs but to a lesser degree. Hyperplasia was found most commonly in the pancreatic islets, and fibro-osseous lesions were observed in several bones. The percentage of lesions increased with age until 20 months. This study shows that KK/HlJ mice demonstrate systemic aberrant mineralization, with greatest frequency in aged mice. The detailed information about histopathological lesions in the inbred strain KK/HlJ can help investigators to choose the right model and correctly interpret the experimental results.